Duplex system ureterocoele: a contemporary review - Mahmoud Marei Marei; Vikrant Kumbhar; William Calvert; Aruna Abhyankar; Caroline MacDonald (Egyptian Pediatric Association Gazette)
Abstract Background Pediatric duplex system ureterocoele (DSU) is a condition managed in specialist centres but will be encountered by pediatricians, pediatric surgeons, and urologists during clinical practice. An understanding of the condition and its current management is important for the care and appropriate referral of neonates and infants with this condition. This study presents a contemporary review of the literature on this diverse condition and presents a suggested pathway for management. There is no dispute the topic needs regional expertise, at least in the UK NHS. Objective To understand the current status of management to evaluate the feasibility of a consensus statement on the management of DSU. Methods A narrative review of the literature was conducted to evaluate current management approaches for duplex system ureterocoele (DSU). Due to heterogeneity in available data, a formal consensus was not feasible, and a descriptive synthesis of current practices and recommendations was undertaken. The authors, using appropriate terms within MEDLINE, described the current literature. Neither a systematic review nor a meta-analysis was possible due to the breadth of the topic and the heterogeneous outcomes recorded. Literature content and analysis were internally validated by the authors. Conclusion The introduction of routine antenatal ultrasonography has changed the understanding of duplex system ureterocoele (DSU), with the natural history becoming evident in the context of asymptomatic DSU. Conservative management (i.e., no intervention) may be appropriate for a proportion of infants with DSU, as some DSUs may have no obstruction and conservative follow-up would suffice, but careful surveillance is necessary as DSU may/can be causative of urosepsis and nephron loss in neonates and infants. Clinicians must be aware of absolute and relative indications for intervention and the various options therewith.